Bilingual Education Method: Teaching Foreign Languages Through Art - Integration of CLIL and ESL/ELL Approaches in Ukrainian Educational Context (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2025)
This article analyzes modern bilingual teaching methods CLIL (Content and Language Integrated Learning) and ESL/ELL (English as Second Language/English Language Learners), which integrate foreign language instruction with other academic subjects. These methodologies are actively implemented in European educational systems and are gradually being introduced in Ukraine. The research identifies key implementation challenges, particularly the mismatch in teacher training and qualification requirements. The authors propose that art serves as an optimal subject for integration with foreign language teaching, as it functions as a practical component that stimulates hands-on creative activities while facilitating vocabulary acquisition and cultural understanding. Unlike subjects such as mathematics, physics, or geography, art is more accessible for language teachers to master and seamlessly integrates into foreign language lessons while revealing cultural aspects of the target language. The study demonstrates that foreign language learning through art not only develops students' communicative and linguistic competencies but also significantly expands their worldview, cultivates appreciation for various art forms (music, painting, literature, architecture, cinema), and provides essential background knowledge for successful intercultural communication. The paper presents positive and negative aspects of these bilingual methods, their impact on educational quality, and proposes practical implementation strategies for modern Ukrainian education. Three detailed lesson plans are provided to illustrate the methodology's application across different educational levels (primary, secondary, and high school).
Keywords: bilingual education; CLIL; ESL/ELL; art integration; foreign language teaching methodology; intercultural communication; Ukrainian education system; creative learning activities